Development of Web Application for Forensic Medical Record program in Road Traffic Accidents - พูลพร, อนุพงษ์; กุลนิเทศ, ณรงค์; คำหล้า, วัชรพงษ์; สังวาระนที, นิศากร; สังวาระนที, ณรงค์ (Journal of Health Science of Thailand, 2022)
The purposes of this study were to develop and evaluate the effectiveness of a Forensic Medical Record Web Application Program for managing forensic medical records in accident and emergency departments using a mobile phone or a portable computer via an internet connection. The expected benefit would be to increase the ability to manage documents more efficiently. The system would require user registration, user management, and user password management including a review of user access right. The study was conducted as a development research comprising of 2 phases. The phase 1 was to study the development of Forensic Medical Record Web Application Program of which the evaluation results from experts found that the developed system could satisfy the needs at a good level as it reduced duplication of medical records; and the information was correct in accordance with the forensic medical principle. Furthermore, it could be used through various browsers without the need to install; and the information could be added, reduced or edited in the system at any time. Phase 2 was the assessment of the Forensic Web Application Program performance. There were 323 people enrolled by purposive sampling who were physicians and registered nurses who worked on forensic medicine in emergency department. They were requested to use and evaluate the application program; and their opinions were assessed by using a set of questionnaire and interview form; and the data were analyzed with descriptive statistics. It was found that the use of the Forensic Web Application Program performance was at satisfactory level (mean=4.00, SD=0.43) because of its convenience and faster operation (mean=4.73, SD=0.47). In conclusions, the Forensic Medical Record Program reduces redundant work and improves the efficiancy of the forensic medical records document management system.